Big Data and central banks. Issue 1 (21st April 2015) - Bholat, David
This commentary recaps a Centre for Central Banking Studies event held at the Bank of England on 2–3 July 2014. The article covers three main points. First, it situates the Centre for Central Banking Studies event within the context of the Bank's Strategic Plan and initiatives. Second, it summarises and reflects on major themes from the event. Third, the article links central banks' emerging interest in Big Data approaches with their broader uptake by other economic agents.